The Joint Effect of hOGG1, APE1, and ADPRT Polymorphisms and Cooking Oil Fumes on the Risk of Lung Adenocarcinoma in Chinese Non-Smoking Females - Xue, Xiaoxia; Yin, Zhihua; Lu, Yao; Zhang, Haibo; Yan, Ying; Zhao, Yuxia; Li, Xuelian; Cui, Zeshi; Yu, Miao; Yao, Lu; Zhou, Baosen (PloS one, 2013)
The human 8-oxoguanine DNA glycosylase 1 (hOGG1), apurinic/apyrimidinic endonuclease 1 (APE1), and adenosine diphosphate ribosyl transferase (ADPRT) genes play an important role in the DNA base excision repair pathway. Single nucleotide polymorphisms (SNPs) in critical genes are suspected to be associated with the risk of lung cancer. This study aimed to identify the association between the polymorphisms of hOGG1 Ser326Cys, APE1 Asp148Glu, and ADPRT Val762Ala, and the risk of lung adenocarcinoma in the non-smoking female population, and investigated the interaction between genetic polymorphisms and environmental exposure in lung adenocarcinoma. We performed a hospital-based case-control study, including 410 lung adenocarcinoma patients and 410 cancer-free hospital control subjects who were matched for age. Each case and control was interviewed to collect information by well-trained interviewers. A total of 10 ml of venous blood was collected for genotype testing. Three polymorphisms were analyzed by the polymerase chain reaction-restriction fragment length polymorphism technique. We found that individuals who were homozygous for the variant hOGG1 326Cys/Cys showed a significantly increased risk of lung adenocarcinoma (OR = 1.54; 95% CI: 1.01-2.36; P = 0.045). When the combined effect of variant alleles was analyzed, we found an increased OR of 1.89 (95% CI: 1.24-2.88, P = 0.003) for lung adenocarcinoma individuals with more than one homozygous variant allele. In stratified analyses, we found that the OR for the gene-environment interaction between Ser/Cys and Cys/Cys genotypes of hOGG1 codon 326 and cooking oil fumes for the risk of lung adenocarcinoma was 1.37 (95% CI: 0.77-2.44; P = 0.279) and 2.79 (95% CI: 1.50-5.18; P = 0.001), respectively. The hOGG1 Ser326Cys polymorphism might be associated with the risk of lung adenocarcinoma in Chinese non-smoking females. Furthermore, there is a significant gene-environment association between cooking oil fumes and hOGG1 326 Cys/Cys genotype in lung adenocarcinoma among female non-smokers.